Chemical and sensorial characterization of spray dried hydroSOStainable almond milk. (12th September 2020) - Lipan, Leontina; Rusu, Bogdan; Simon, Elemer L; Sendra, Esther; Hernández, Francisca; Vodnar, Dan C; Corell, Mireia; Carbonell‐Barrachina, Ángel
Abstract: BACKGROUND: Water scarcity is a worldwide problem that leads to environmental and economic issues. Agriculture is one of the main consumers of water for irrigation and fertilization and almond is the major tree nut crop in the Mediterranean area. Furthermore, there is a continuous growing demand for healthy, vegan and sustainable products. Consequently, the present study aimed to chemically characterize almond milk powder enriched with probiotics manufactured from hydroSOStainable almonds (i.e. generated under water stress conditions). Almond milk powder enriched with probiotic bacteria was produced with almonds grown under optimal irrigation conditions (100% of the crop evapotranspiration) and was chemically compared to the samples made from hydroSOStainable almonds. Antioxidant activity, total phenolic content (TPC), minerals, organic acids and sugars, fatty acids, and descriptive sensory analysis were evaluated. RESULTS: The results showed that almond milk powder produced from hydroSOStainable almonds had a higher content of TPC, polyunsaturated fatty acids (PUFAs), PUFAs/saturated fatty acids (SFAs) ratio and PUFAs/monounsaturated fatty acids ratio, as well as almond and nutty flavors. Moderate and sustained deficit irrigation leads to powders with a higher content of PUFAs and PUFAs/SFAs ratio, which are parameters of utmost importance for health. CONCLUSION: Using these strategies, between 66% and 76% of the irrigation water can be saved, producing hydroSOStainable almond milk powder higher in TPC and PUFAs, as well as positive sensory attributes, compared to that from fully irrigated almonds. These findings may have a positive impact in both agriculture and food industry, allowing water savings and high quality and sustainable food products to be obtained. © 2020 Society of Chemical Industry